SAT0025 THE EFFECT OF DIMETHYL FUMARATE ON PLASMABLAST DIFFERENTIATION TRANSCRIPTIONAL PROGRAMMES IN SYSTEMIC LUPUS ERYTHEMATOSUS. (June 2019) - Mauro, Daniele; Rivellese, Felice; Manou-Stathopoulou, Sotiria; Goldmann, Katriona; Pyne, Debasish; Ciccia, Francesco; Pitzalis, Costantino; Lewis, Myles
Abstract : Background: Dimethyl fumarate (DMF), is an immunomodulatory drug approved for the treatment of Multiple Sclerosis (MS) and Psoriasis. The exact mechanism of action of DMF is not entirely known. Anti-inflammatory and immunomodulatory effects have been observed, including the upregulation of NRF-2, the inhibition of TIGAR and the block of the E2 ubiquitin-conjugating enzyme UBEL3. Further evidence from MS patients suggests a modulation on B cell activation. Although beneficial effects of DMF have been observed in animal models of lupus nephritis and limited cases human cutaneous lupus, the effect of DMF on B cell maturation transcriptional programmes in systemic Lupus Erythematosus (SLE) has not been fully investigated. Objectives: To examine the effect of DMF on SLE plasmablast differentiation and identify the transcriptomic changes in cultured SLE B cells after DMF administration. Methods: B cells were isolated from the peripheral blood of SLE patients (n=15) by negative magnetic sorting. B cell differentiation toward plasmablasts was induced in-vitro by stimulation with TLR-7 agonist Resiquimod, CD40L, IL-2, IL-10 and IL-15 for 5 days in the presence of DMF 25 uM or vehicle, added 24h after plating. IgG and IgM production were quantified in the supernatant by ELISA. In-vitro differentiated B cells were immunophenotyped by 10-colour flow cytometry in order to identify Naïve (CD27 - IgD + ), Memory (CD27 + IgD - ), IgD + Memory (CD27 + IgD + ), Double Negative (DN) (CD27 - IgD - ) B cells, pre-plasmablasts (pre-PBs) (CD27 +, CD20low, CD38 - ) and plasmablasts (PBs) (CD27 +, CD20 low, CD38 + ). Naïve B cells and PBs from 3 patients were isolated by fluorescence-activated cell sorting and underwent to RNA-sequencing followed by pathway analysis. Results: DMF administered from day 2 led to a relative increase in the percentage of Naïve B cells (p=0.002) and a substantial reduction in Memory B cells (p=0.005), while the proportion of DN cells and IgD + Memory B cells were not altered. DMF reduced the percentage of PBs (p=0.003), in contrast, the percentage of pre-PBs was significantly increased (p=0.006). Consistently, IgG and IgM secretion were significantly reduced (p<0.001). DMF treatment induced significant transcriptional changes in both PBs and Naïve B cells, with 269 and 652 genes modulated in PBs and Naïve B cells, respectively (Paj <0.05). Pathway analysis highlighted the downregulation of a number of pathways: detoxification of reactive oxygen species, transcriptional regulation of cell cycle inhibitor p21, mitophagy and Pink/Parkin Mediated mitophagy, interleukin-12 signalling, TP53 and p53 regulation, PERK mediated endoplasmic unfolded protein response, and NF-kB mediated cell survival. Conversely, pathways related to epigenetic regulation, RUNX1 signalling, Rho and GTPase signalling were upregulated. Conclusion: Our results show that Dimethyl Fumarate exerts a significant inhibition on SLE plasmablast differentiation and antibody production. The transcriptomic analysis allowed to dissect B cell transcriptional programmes activated in the context of autoimmune B cell differentiation in SLE. The transcriptional perturbations induced by DMF highlighted some of the gene expression pathways necessary for plasmablast differentiation and survival. In addition, these data provide new insight into DMF pharmacodynamics and may support the repositioning of DMF in the treatment of SLE. Disclosure of Interests: Daniele Mauro: None declared, Felice Rivellese: None declared, Sotiria Manou-Stathopoulou: None declared, Katriona Goldmann: None declared, Debasish Pyne: None declared, Francesco Ciccia Grant/research support from: CELGENE, PFIZER, Consultant for: UCB, NOVARTIS, CELGENE, PFIZER, LILLY, Paid instructor for: UCB, NOVARTIS, CELGENE, PFIZER, LILLY, JANSSEN, Speakers bureau: UCB, NOVARTIS, CELGENE, PFIZER, LILLY, JANSSEN, ROCHE, AMGEN, Costantino Pitzalis Grant/research support from: Celgene, Myles Lewis Grant/research support from: Celgene